Long-term monitoring confirms limitations of recruitment and facilitation and reveals unexpected changes of the successional pathways in a glacier foreland of the Central Austrian Alps - Brigitta Erschbamer; Ruth Niederfriniger Schlag; Pau Carnicero; Rüdiger Kaufmann (Plant Ecology, 2023)
On a glacier foreland of the Central Austrian Alps, a permanent plot study was performed to investigate the successional pathway on two moraines. We expected that the pioneer stage deglaciated for 25 years will converge to an early successional stage after another 25 years and the early stage deglaciated for 40 years will show trends toward a late successional stage. Different dynamics of species occurrence such as colonization/persistence and cover increase/decrease, were anticipated. Twenty plots of 25 × 25 cm were established in 1996 on each successional stage by selecting vegetated and bare ground plots to account for impacts of facilitation on seedling recruitment. We expected seed and establishment limitations, therefore, also effects of sowing were studied on sown and control plots. Species enrichment occurred on all control and sown plots of both stages. However, the pioneer stage did not converge to an early successional stage as it was expected. On the early successional stage, only on sown plots a development toward a late successional stage was found. Bryophyta were the most efficient colonizers on all plots together with the lichen Stereocaulon alpinum at the pioneer stage and the sown species Anthyllis vulneraria ssp. alpicola at the early successional stage. The pioneer species Saxifraga oppositifolia was still present after 25 years on the pioneer and early successional stages, although its cover significantly decreased. We conclude that seed and establishment limitations, drought, facilitation deficits, and ageing of individuals are the essential drivers on the studied glacier foreland, creating ‘quasi-stationary’ communities.